Recent Advances on Phagocytic B Cells in Teleost Fish - Wu, Liting; Qin, Zhendong; Liu, Haipeng; Lin, Li; Ye, Jianmin; Li, Jun (Frontiers in Immunology, 2020)
The momentous discovery of phagocytic activity in teleost B cells has caused a dramatic paradigm shift that phagocytosis was performed by professional phagocytes derived from a common myeloid progenitor cells, such as macrophages/monocytes, neutrophils and dendritic cells. Recent advances on phagocytic B cells and their microbicidal ability in teleost fish position the B cells at the crossroads for bridging innate with adaptive immunity. Most importantly, increasing experimental evidences demonstrate that in both teleosts and mammals, phagocytic B cells can recognize, uptake, and destruct particulate antigens, and then present those processed antigens to CD4+ T cells and to elicit adaptive immune responses, and the phagocytosis is mediated by pattern recognition receptors and involved multiple cytokines. Thus, current findings collectively indicate that teleost phagocytic B cells, as well as their counterpart mammalian B1-B cells, can be considered as one kind of professional phagocytes. The aim of this review is to summarize recent advances of teleost phagocytic B cells in particular focus on the recognizing receptors, and modulating mechanisms of phagocytic B cells and the process of antigen presentation to T cell activation. We also attempt to provide new insights into the understanding of the adaptive evolution of teleost fish phagocytic B cell for its innate and adaptive roles.